Ruminal fermentation response and nitrogen retention from sheep fed rumen undegradable protein - Puastuti, Wisri; Yulistiani, D; Mathius, I.W (Indonesian Journal of Animal and Veterinary Sciences, 2012)
The utilization of rumen undegradable protein, could increase supply of amino acids in small intestine to meet host protein requirement. To increase the utilization of feed protein, feed protein source which is highly degradable should be protected from degradation in the rumen. The objective of the study was to increase nitrogen retention through substitution of fish meal protein with soy bean meal protected by banana stem juice observed from rumen fermentation activities. The study used 18 late pregnant Sumatera Composite breed ewes. Rations consisted of fresh chopped elephant grass, supplemented with a commercial concentrate and mineral block in the form of Comin plus and different types of protein supplement as treatment diets. The type of protein supplements were: soya bean meal (RK), soy bean meal protected with banana stem juice (RKT) and fish meal (RTI). Treatment diets were offered during late pregnancy (from two months before to two months after partus), two weeks adaptation period was carried out before data recording. Design of the study used randomized complete block design. Results of the study show that rumen ammonia concentration in sheep fed on RKT was not significantly different either from RTI or from RK, however, the nitrogen retention was significantly (P < 0.05) different among the treatments (4.92 g/h vs 12.52 g/h; 17.11 g/h). Total VFA production or the proportion of C3, iC4, iC5 and nC5 was not significantly different (P > 0.05), however, proportion of C2 and nC4 was significantly different between diet treatment. Methane emission was higher (70.3 mM or 37.2% higher from total energy VFA) in diet RKT which is indicated that fermentation system was not efficient. It can be concluded the higher rumen ammonia concentration and lower nitrogen retention in protected soy bean meal supplement indicated that soy bean meal protected by banana stem juice in the ration was not able to substitute fish meal protein which is resistance from degradation in the rumen. Key Words: Sheep, Rumen Fermentation, Rumen Undegradable Protein